Benthic Macroinvertebrates as Ecological Indicators: Their Sensitivity to the Water Quality and Human Disturbances in a Tropical River - Tampo, Lallébila; Kaboré, Idrissa; Alhassan, Elliot H.; Ouéda, Adama; Bawa, Limam M.; Djaneye-Boundjou, Gbandi (Frontiers in Water, 2021)
Macroinvertebrates metrics are helpful tools for the assessment of water quality and overall aquatic ecosystem health. However, the knowledge of their degree of sensitivity and the most reliable metrics for the bioassessment programme development is very poorly studied in Togo. This study aimed to test the sensitivity of metrics calculated at family and genera level. A total of twenty-one water quality parameters and macroinvertebrates’ data were collected during three periods in twenty sampling sites within Zio River. The canonical correspondence analysis (CCA), factorial analysis (FA) and Spearman correlation analysis were conducted on water quality parameters and macroinvertebrates’ data. The results reveal that macroinvertebrate structure and composition were affected by water quality parameters related to human disturbances. In this study, three groups of macroinvertebrate communities were majorly identified including sensitive taxa such as Ephemeroptera, Plecoptera, Tricoptera and Odonata (EPTO) taxa, the resistant or resilient taxa such as Oligochaeta, Hirudinea, Diptera and Pulmonates (OHDP) taxa, and tolerant taxa such as Prosobranchia, Bivalvia, Lepidoptera, Heteroptera and Coleoptera (PBLHC). All the thirteen macroinvertebrate-based metrics were found to be sensitive in the detection of water quality and human disturbance gradients. However, metrics related to EPTO and the tolerance measure (MMIZB, ASPT, BMWP) are the most robust in discrimination of pressure gradients. This study reveals that macroinvertebrates are sensitive and can be used for the bioassessment programme development at order, family or genera taxonomic level.